A COMPARATIVE STUDY OF SPRING TRITICALE VARIETIES IN THE WESTERN SIBERIAN FOREST-STEPPE ZONE UNDER DIFFERENT CONDITIONS OF VEGETATION - A. Cheshkova; P. Stepochkin; A. Aleynikov; I. Grebennikova; D. Chanyshev (Вавиловский журнал генетики и селекции)
Spring triticale (x Triticosecale Wittmack) for Western Siberia is new and poorly studied culture. The objective of this study was to investigate the potential of spring triticale varieties and breeding lines and their adaptation to diferent conditions in Western Siberia. A ield experiment was conducted in Novosibirsk region, Russia in 2014. The experiment included seven spring triticale genotypes: the elite variety Ukro, three mutant forms of the facultative type of development (Sirs 57/2/4, Cecad 90/5, О.312/38) and three hybrids (Sirs 57/2/4 x Ukro, Ukro x K-3881, the complex hybrid winter wheat Filatovka x winter rye Korotko stebelnaya 69304 x Sirs 57/2/4). They were studied at two sowing rates (400 seeds per m2 and 800 seeds per m2) and on two sowing dates (15 May 2014 and 27 May 2014). The following attributes were measured: grain yield, number of ears, plant height, yield components (ear length, number of spikelets per ear, number of grains per ear, grains weight per ear) and yield quality (1 000-grain weight and test weight of one-liter grain volume). The three-factor analysis of variance revealed that sowing rate efect explained the major part of the total experimental variation in almost all of the traits, except 1 000-grain weight and test weight, the variation of which was determined predominantly by genotype efect. The highest grain productivity of varieties was obtained for the 15 May sowing date at the 400 seeds per m2 sowing rate. The three mutant forms used in the experiment showed a lower level of adaptability in comparison with the variety Ukro.